2012
DOI: 10.1007/s10433-012-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of change in self-rated health among older adults in Europe: a longitudinal perspective based on SHARE data

Abstract: The present study aims at detecting factors which may predict a decline or an improvement in self-rated health (SRH) of older adults (persons aged 50 or higher) among socio-demographic characteristics, physical and mental health indicators and risky health behaviours. In the analysis, multinomial logistic regression models are applied to data from waves 1 and 2 of the Survey of Health Ageing and Retirement in Europe (carried out about 3 years apart); persons who report a decline or an improvement in SRH at wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
38
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 46 publications
5
38
4
2
Order By: Relevance
“…However, this resembles prior reports from studies conducted elsewhere, which have pointed out not significant relationships between education and the number of chronic conditions and multimorbidity in multivariable-adjusted models [37-40]. Thus, a study including individuals aged ≥18 years reported a non-significant association between education and multimorbidity [36], whereas a large cohort study among elderly people aged 50–75 years old reported that, upon multivariable-adjustment, the association of multimorbidity with education weakened in men, whereas in women it was not statistically significant [41].…”
Section: Discussionsupporting
confidence: 88%
“…However, this resembles prior reports from studies conducted elsewhere, which have pointed out not significant relationships between education and the number of chronic conditions and multimorbidity in multivariable-adjusted models [37-40]. Thus, a study including individuals aged ≥18 years reported a non-significant association between education and multimorbidity [36], whereas a large cohort study among elderly people aged 50–75 years old reported that, upon multivariable-adjustment, the association of multimorbidity with education weakened in men, whereas in women it was not statistically significant [41].…”
Section: Discussionsupporting
confidence: 88%
“…Generally, advanced age is related to more chronic diseases, more depression and a lower level of functional ability, which consequently induce poorer SRH. Physical activity, 15,49 loneliness, 55 and social support 56 have been regarded as determinants of SRH; however, they were not significant in the multinomial logistic regression models in the present study. 48 The present study found that the participants aged 60-69 years were more likely to rate their health as good, whereas there were no significant differences between the participants aged 70-79 years and those aged 80 years and older regarding SRH.…”
Section: Discussioncontrasting
confidence: 80%
“…Various aspects of objective health are important predictors of subjective health (Pinquart, 2001), for example, physical health, consisting of perceived symptoms and the number of medical conditions, is strongly related to SRH and is seen as a predictor of SRH (Mora et al, 2008). Poorer physical health is related to lower SRH (Eriksson, Unden, & Elofsson, 2001; French, Sargent-Cox, & Luszcz, 2012; Leinonena, Heikkinena, & Jylhä, 2001; Verropoulou, 2012). Nevertheless, aging people are often able to adapt to a decline in physical health, and therefore not always result in a decline in SRH (Leinonena et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SRH is also based on culture and may be affected by the country of residence. In Europe, there are major variations in rating and perspectives of health among countries (Verropoulou, 2012). A more favorable or more negative rating of health is part of the character of individuals and the environment in which they live and depends on the aspects that an individual ascribes to her health (Brissette, Leventhal, & Leventhal, 2003; Jylhä, 2009).…”
Section: Introductionmentioning
confidence: 99%